Notas sobre el uso de la fauna silvestre en Catemaco, Veracruz, México. - Morales Mávil, Jorge E.; Villa Cañedo, Jorge T. (Instituto de Ecología, A.C., 1998)
The objectíve of this paper was to know the fauna used (terrestríal vertebrates) in Catemaco, Veracruz. The Information was obtained through surveys directed to sports huntera, restaurant chiefs, wizards, furriers and ambulant merchants. A list of species of hunt, and the sites preferred by the hunters, wíthin the Los Tuxtlas región was obtaíned. In addition, a list of 19 species used for nutritional consumption was obtained. The species with greater praference were the tepezcuintle (Agouti paca), armadillo (Dasypus novemcinctus) and two tortoises (Staurotypus tríporcatus and Trachemys scrípta). This work aiso provides Information on the curative and magic uses of several wild vertebrates species and about the commercial utilization of live animáis or their body parts used for hand made artisanal objects.